2019
DOI: 10.3145/epi.2019.sep.07
|View full text |Cite
|
Sign up to set email alerts
|

Communicating corporate social responsibility issues on Facebook’s corporate fanpages of Latin American companies

Abstract: By exploring the strategic use of social media for 250 of Fortune's Most Admired U.S. Companies on Facebook, Twitter, and YouTube, this study creates a benchmark by which companies can use to gauge their involvement in the three dominant social media platforms. Results found that 91% of the companies utilized at least one social media platform. YouTube was the most commonly adopted social media followed by Twitter then Facebook. Overall, 30% of companies in this study provided a social media code of conduct in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
12

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 51 publications
0
4
0
12
Order By: Relevance
“…Por ello, es de suma importancia que las empresas mantengan una comunicación constante con sus públicos, para así evitar que la situación crítica se agrave (Emmy et al, 2016). En este sentido, la RSC es una actividad legitimadora para las organizaciones, ya que ayuda a mejorar la reputación (Shin et al, 2021;Zeler & Capriotti, 2019), y ganar fortaleza en tiempos de crisis (Xifra, 2020).…”
Section: La Comunicación En Twitter Como Valor Intrínseco De La Rsc E...unclassified
See 1 more Smart Citation
“…Por ello, es de suma importancia que las empresas mantengan una comunicación constante con sus públicos, para así evitar que la situación crítica se agrave (Emmy et al, 2016). En este sentido, la RSC es una actividad legitimadora para las organizaciones, ya que ayuda a mejorar la reputación (Shin et al, 2021;Zeler & Capriotti, 2019), y ganar fortaleza en tiempos de crisis (Xifra, 2020).…”
Section: La Comunicación En Twitter Como Valor Intrínseco De La Rsc E...unclassified
“…Si bien varios autores destacan el impacto positivo de la comunicación de la RSC para la reputación (González-Rodríguez et al, 2015;Illia et al, 2017;Ros & Castelló, 2012a;Vogler & Eisenegger, 2020;Zeler & Capriotti, 2019), hay otros que ofrecen una visión crítica sobre el tema mediante el uso cada vez más preponderante del llamado greenwashing por parte de las empresas (que sugiere tener actitud responsable sin que exista un comportamiento real que así lo justifique), con el fin de tratar de desviar la atención de las deficiencias ambientales y sociales, y así construir capital de reputación corporativa (Elving & Van Vuuren, 2011;Lyon & Maxwell, 2011;Torelli et al, 2020;Vollero et al, 2016).…”
Section: La Comunicación En Twitter Como Valor Intrínseco De La Rsc E...unclassified
“…Other studies have shown that there is no real dialogue because social networks are used in a unidirectional way (Zeler & Capriotti, 2019). However, the literature has shown that the mere presence of companies in social networks leads to a greater interest in the performance of a key intangible such as CSR and an increase in the company's predisposition to dialogue (Barbeito-Caamaño & Chalmeta, 2020).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Pese a todo, diversos estudios han evidenciado que a las empresas todavía les queda mucho por hacer en el uso de los medios sociales en aras de la transparencia, la conversación y la coherencia entre el decir y el hacer (Gómez-Vásquez, 2013;Aced-Toledano y Lalueza-Bosch, 2016;Mariano-Da-Rocha-Barichello y Scheid, 2017;Capriotti, Zeler y Oliveira, 2019;Zeler y Capriotti, 2019). El vídeo puede ser un formato óptimo para la comunicación del compromiso de la marca para con la sociedad y para la construcción de una relación con los usuarios basada en la escucha social (Costa-Sánchez y Túñez-López, 2019, p. 224).…”
Section: Youtube En La Comunicación Persuasiva Integradaunclassified